2021
DOI: 10.1080/08827508.2021.1890591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Additives on Rheological Properties of Dry Ground Ore - a Comparative Study

Abstract: It is well documented that chemical additives (grinding aid "GA") during grinding can increase mill throughput, reduce water and energy consumption, narrow the particle size distribution of products, and improve material flowability. These advantages have been linked to their effects on the rheology, although there is a gap in understanding GA effectiveness mechanism on the flow properties. The present study aims to fill this gap using different GAs (Zalta™ GR20-587, Zalta™ VM1122, and sodium hydroxide) throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…SE represents the interparticle interactions due to cohesive forces, which are highly dependent on particle shape, texture, and size. Lower SE means fewer interparticle forces and lower degree of cohesion (Chipakwe, Hulme‐Smith, Karlkvist, Rosenkranz, & Chelgani, 2021; Gnagne, Petit, Gaiani, Scher, & Amani, 2017; Nan, Ghadiri, & Wang, 2017). No significant difference was observed among the three flours in terms of SE.…”
Section: Resultsmentioning
confidence: 99%
“…SE represents the interparticle interactions due to cohesive forces, which are highly dependent on particle shape, texture, and size. Lower SE means fewer interparticle forces and lower degree of cohesion (Chipakwe, Hulme‐Smith, Karlkvist, Rosenkranz, & Chelgani, 2021; Gnagne, Petit, Gaiani, Scher, & Amani, 2017; Nan, Ghadiri, & Wang, 2017). No significant difference was observed among the three flours in terms of SE.…”
Section: Resultsmentioning
confidence: 99%
“…In the cement industry, the use of grinding aids (GAs) has been examined as a promising alternative to address these issues 3 , 4 . Chemical additives or GAs would be considered as any substance (less than 0.25 wt.%) added to the mill to reduce energy consumption 5 7 . GAs have been mostly examined in the cement industry and are still not widely practiced in mineral beneficiation plants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated the benefits of polysaccharide-based GA (PGA) as a green chemical additive in improving mineral grinding performance 10 and material rheology 5 . However, the high cost and purported effects on downstream processes as a result of the potential synergistic interaction of the GAs and flotation reagents limit their applications.…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of grinding aids on improving product fineness has been observed in the literature [10,[41][42][43]. The improvement in fineness points to better grinding due to improved material flowability resulting from the reduction in agglomeration [5,6,41,44,45]. In terms of uniformity, which generally measures PSD, the introduction of AAG results in a narrow PSD width (lower number uniformity).…”
Section: Grinding Performancementioning
confidence: 85%